2014
DOI: 10.1002/mawe.201400189
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of tungsten and molybdenum carbide onto the surfaces of disperse dielectric and semiconductor materials

Abstract: The systems suitable for a high‐temperature electrochemical synthesis on the surfaces of diamond, boron nitride, and silicon and boron carbides were selected on the basis of the thermodynamic analysis of the reactions of dielectrics and semiconductors with ionic melts and the study of their electrochemical behavior. Electroplating of the grains of dielectrics and semiconductors with molybdenum carbide favors the increase in their breaking load and wettability and in the efficiency of tools. Thermodynamic calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…The assumptions used to obtain formula (20) are similar to those, which were used previously in [3,4]. Comparing (20) with the results obtained in [4] (see formula (29)), we obtain the value of the constant ρ p , which by its physical meaning is the average value of states in the valence band of the electrode materials in heterogeneous charge transfer…”
Section: Kinetics Of the Elementary Act Of Electron Transfer At The S...mentioning
confidence: 71%
See 1 more Smart Citation
“…The assumptions used to obtain formula (20) are similar to those, which were used previously in [3,4]. Comparing (20) with the results obtained in [4] (see formula (29)), we obtain the value of the constant ρ p , which by its physical meaning is the average value of states in the valence band of the electrode materials in heterogeneous charge transfer…”
Section: Kinetics Of the Elementary Act Of Electron Transfer At The S...mentioning
confidence: 71%
“…It should be stressed that our results are of purely theoretical nature, but it is interested to compare them with experimental data, specifically, with the results of experiments of Shapoval et al concerning the possibility of drawing on natural and synthetic diamonds the galvanic coating without preliminary depositing a conducting film [17][18][19][20]. The authors of the experiments have not proposed a convincing interpretation of the results obtained.…”
Section: Kinetics Of the Elementary Act Of Electron Transfer At The S...mentioning
confidence: 81%
“…Electrochemical nanotechnologies are developed in Ukraine, in particular, the electrodeposition of nanostructured coatings and nanopowders by the electrolysis of ionic melts. The first direction includes coatings of molybdenum and tungsten carbides on grains of dispersed dielectric and semiconductor materials [23,24]. In the second direction, nanopowders of carbides [25] and silicides [26,27] of refractory metals are determined.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…Increased interest in the development of new and effective methods for obtaining refractory compounds – carbides, borides, silicides, alloys and intermetallic compounds of metals of IV–VI B groups is dictated by their use for the needs of modern technology . Comparative analysis of existing methods for the synthesis of metal‐like refractory compounds showed that one of the most promising, but so far little studied is the method of high‐temperature electrochemical synthesis .…”
Section: Introductionmentioning
confidence: 99%